Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Perilaku Inovatif Karyawan (Studi Kasus di PT. Bank Danamon Indonesia) - Ryani Dhyan Parashakti; Mochamad Rizki; Lisnatiawati Saragih (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
This study aims to analyze the impact of Transformational Leadership and Organizational Culture into Innovative Behaviour in PT Bank Danamon Indonesia. Sample data were taken from questionaires that were distributed among employees of PT Bank Danamon Indonesia. Data were analysed with structural equation modeling (SEM). The result shows that transformational leadership and organisational culture have signficant impact toward innovative behavior in PT Bank Danamon Indonesia. It is advisable that further research might use more in depth information in order to have more comprehensive and significant information. The results of the t-test results of all the variables that affect the innovation, companies can improve organizational culture with a characteristic which is upheld by the organization and become a role model for the organization. Transformational leadership is concerned with the interests shared by explaining the importance of the company's goals so that members willing to subordinate his personal interests. In terms of internal and external situation of the organization, transformational used in terms of strategic and not raw.